First Grade High School English Text Book Evaluation: Prospect I - Mohammad Ahmadi Safa; Shadi Donyaee; Shilan Sohrabi; Mojtaba Farahani; Dayan Khasemi; Elahe Saeedpanah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study set out to evaluate a rather newly developed textbook entitled "Prospect I". The textbook is developed as the main text for the nationwide application at the first grade of high school English courses by the Iranian ministry of education. To this end, a researcher-made questionnaire was developed and pilot tested.  Bartlett's test of Sphericity, Keiser-Meyer-Olkin sampling adequacy measure, exploratory factor analysis and factor loadings, and Cronbach's Alpha measure of internal consistency were all run on the pilot study data, and the results verified acceptable levels of validity and reliability for the questionnaire. The validated questionnaire was given to 188 high school English teachers chosen based on convenience sampling procedure from seven provinces of the country. Moreover, 146 teachers sat for a semi-structured interview. The questionnaire and interview  data analyses results revealed that the participating teachers were not satisfied with several aspects of the text including layout and design, the exercises and activities, the integration of the four skills, teachers  book, grammar, vocabulary, language functions, and the proposed teaching methodology of the text.